Social and Psychological Support for Personnel in Organisations: Work-Life Balance Programmes (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The study aimed to explore the work-life balance concept, assessing the level and the peculiarities of work-life balance.Background: The paper covers the psychological reconstruction of the concept of "the work-life balance" in terms of its implicit understanding and differentiated diagnosis.Method: The main research methods are: theoretical – the study of literature on the research problem; empirical – a study on the methodology for assessing psychological well-being, as well as methods of descriptive and analytical statistics.Results: It has been designed an inventory based on 16 statements divided into the work-life balance components by means of the factor analysis. Satisfaction with work and family roles have been found to have additive effects on happiness, life satisfaction, and perceived quality of life. The basic strategies in social and psychological programs in organisations have been analysed as focus strategies, "resource/refusal" strategies, adaptive strategies. Adaptive strategies are the ones helping to adapt to problems arising at work or/and at home.Conclusion: Empirical findings suggest that involvement in multiple roles can improve psychological and mental health by buffering negative effects such as reduced. The use of individual adaptive strategies with the resource increase strategy perfectly contributes to the work-life balance achievement.